2018
DOI: 10.1111/bph.14161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of imidazoline I2 receptor agonist‐induced antinociception in rats: involvement of monoaminergic neurotransmission

Abstract: Antinociception induced by I receptor agonists was mediated by serotonergic and noradrenergic mechanisms with 5-HT , 5-HT and α -adrenoceptor being particularly important. In contrast, the hypothermic and discriminative stimulus effects of I receptor agonists were mediated by distinct, independent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…Several I 2 receptor agonists such as 2-BFI and BU224 and the novel I 2 receptor agonist CR4056 have been shown to inhibit human recombinant MAO A activity in a concentration-dependent manner, and in vivo these drugs caused marked increases in norepinephrine and serotonin content in the rat cerebral cortex and lumbar spinal cord (Ferrari et al, 2011;see also Jones et al, 2007). Li's group has examined the involvement of the monoaminergic system in 2-BFI-and CR4056-induced antinociception in two chronic pain rat models: CFA-induced inflammatory pain and CCI-induced neuropathic pain (Siemian et al, 2018). 2-BFI induced dose-dependent antiallodynia in CCI rats; pretreatment with the selective serotonin reuptake inhibitor fluoxetine or the norepinephrine reuptake inhibitor desipramine dosedependently and significantly enhanced the effects of 2-BFI and shifted the 2-BFI dose-effect curve leftward (Siemian et al, 2018).…”
Section: Pharmacological and Neurobiological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several I 2 receptor agonists such as 2-BFI and BU224 and the novel I 2 receptor agonist CR4056 have been shown to inhibit human recombinant MAO A activity in a concentration-dependent manner, and in vivo these drugs caused marked increases in norepinephrine and serotonin content in the rat cerebral cortex and lumbar spinal cord (Ferrari et al, 2011;see also Jones et al, 2007). Li's group has examined the involvement of the monoaminergic system in 2-BFI-and CR4056-induced antinociception in two chronic pain rat models: CFA-induced inflammatory pain and CCI-induced neuropathic pain (Siemian et al, 2018). 2-BFI induced dose-dependent antiallodynia in CCI rats; pretreatment with the selective serotonin reuptake inhibitor fluoxetine or the norepinephrine reuptake inhibitor desipramine dosedependently and significantly enhanced the effects of 2-BFI and shifted the 2-BFI dose-effect curve leftward (Siemian et al, 2018).…”
Section: Pharmacological and Neurobiological Mechanismsmentioning
confidence: 99%
“…Li's group has examined the involvement of the monoaminergic system in 2-BFI-and CR4056-induced antinociception in two chronic pain rat models: CFA-induced inflammatory pain and CCI-induced neuropathic pain (Siemian et al, 2018). 2-BFI induced dose-dependent antiallodynia in CCI rats; pretreatment with the selective serotonin reuptake inhibitor fluoxetine or the norepinephrine reuptake inhibitor desipramine dosedependently and significantly enhanced the effects of 2-BFI and shifted the 2-BFI dose-effect curve leftward (Siemian et al, 2018). The dopamine reuptake inhibitor GBR12909 failed to alter the antiallodynic effect of 2-BFI under the same condition.…”
Section: Pharmacological and Neurobiological Mechanismsmentioning
confidence: 99%
“…Peripheral venous blood was taken from any easily accessible peripheral vein at three time-points post ROSC: 1 h, 2 days and 7 days. Plasma was obtained [13,14] and frozen at − 80°C for further experiment [15].…”
Section: Data Collection and Blood Samplingmentioning
confidence: 99%
“…Remarkably, I2 receptors play a role in the same events that link obesity with impaired sensory behavior. Animal studies have shown that putative I2 receptor agonists inhibit neuroinflammation by decreasing spinal microglia activation, and can restore monoaminergic transmission in the descending pain systems 10,34,35 .…”
Section: Discussionmentioning
confidence: 99%